2017
DOI: 10.5210/fm.v22i5.7102
|View full text |Cite
|
Sign up to set email alerts
|

How do Saudi youth engage with social media?

Abstract: With the global growth of social media platforms, there are questions as to how regional cultural factors shape online engagement. Focusing on young Saudi Arabian users of some of the more popular platforms such as Instagram, Facebook, and Snapchat, this article uses Hofstede’s cultural dimensions to assess how cultural and religious factors are shaping and constraining online social media engagements. Using interviews, questionnaires, and analysis of individual profiles, this paper discusses some of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The present study found that most respondents used social media very often. The International Telecommunication Union has noted that Saudi Arabia is one of the top ten countries using information and communication technology ( 30 ). There have been significant increases in social media users in Saudi Arabia over the past few years, reaching 23 million users, an amount equal to 70% of the population ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that most respondents used social media very often. The International Telecommunication Union has noted that Saudi Arabia is one of the top ten countries using information and communication technology ( 30 ). There have been significant increases in social media users in Saudi Arabia over the past few years, reaching 23 million users, an amount equal to 70% of the population ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Saudi study by Stanger et al (2017) provided invaluable insight into social media habits of an Arabian Gulf country with a comparative cultural landscape to Kuwait. Kuwait is collectivist and patriarchal where family is regarded as a priority, and people define themselves in terms of the context in which they belong, such as by tribes, families from patriarchal lineage, and the country they belong to.…”
Section: Kuwait Arab Culture Gender and Social Mediamentioning
confidence: 99%
“…Thus, the sharing of information on social media is linked to one's reputation within society. (Dinkha et al 2008, Al-Jassar 2009, Dakhli et al 2013, EEAS 2016, Stanger et al 2017.…”
Section: Kuwait Arab Culture Gender and Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In this region, some researchers were concerned in exploring how individuals' awareness toward privacy for online social networks (Snapchat) appose to their protective actions [9]. Moreover, in [10], the study was about examining how Saudi youth engagements with online social networks are formed and constrained within the cultural and religious aspects of this region. Meanwhile, others were assessing the effectiveness of Snapchat in raising the awareness of breast cancer among Saudi female students in the Dammam region [11].…”
Section: Introductionmentioning
confidence: 99%